THE HEXAGON OF DISINFORMATION: A FRAMEWORK FOR EMPIRICAL RESEARCHES - Hoffmann da Silva, Maurílio Luiz (AoIR Selected Papers of Internet Research, 2026)
Disinformation has consolidated as a complex contemporary phenomenon. However, its academic study often remains fragmented, with research focusing on isolated aspects such as content or network structures while neglecting the political and economic incentives that sustain the system. This methodological fragmentation highlights a significant gap. To address this, this paper introduces the "Hexagon of Disinformation," a theoretical-methodological framework designed to guide the systemic and integrated empirical analysis of disinformation.The model is structured into six interconnected and interdependent dimensions: material, social, technological, economical, political, and institutional. Theoretically, the framework is grounded in an articulation of Fairclough's (1992, 2015) theory of discourse as social practice and Recuero's (2024) systemic perspective. This approach conceptualizes disinformation not as simple "false content," but as a discursive action embedded in power struggles and as a complex system analyzable as an object, process, and effect.The framework’s primary contribution is its systemic nature, inviting researchers to investigate the relationships of interdependence between the dimensions. The paper details each dimension, including the material (linguistic strategies), social (group dynamics), technological (platforms, algorithms), economical (monetization), political (polarization, populism), and institutional (attacks on public trust). The value of the Hexagon lies in analyzing the connections between these porous dimensions. By emphasizing interconnectedness, the framework offers a versatile tool for a more holistic understanding of the disinformation ecosystem.